2019
DOI: 10.1186/s12882-019-1504-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk groups of infectious spondylitis in patients with end-stage renal disease under hemodialysis: a propensity score-matched case-control study

Abstract: Background Patients with end-stage renal disease (ESRD) under hemodialysis (HD) are at greater risks of infectious spondylitis (IS), but there is no reliable predictor that facilitate early detection of this relatively rare and insidious disease. Methods A retrospective review of the medical records from patients with ESRD under HD over a 12-year period was performed at a tertiary teaching hospital, and those with a first-time diagnosis of IS were identified. A 1:4 prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous studies showed that the most common discitis-related disease was diabetes mellitus in 18 patients (16.6%), followed by ESRD in 10 (9.25%) (14). A systematic review and other reports concluded that ESRD has a positive relationship with discitis through repeated vascular access (15,16). Uremia in ESRD may alter immune status characterized by immunodepression and increased likelihood of infection, especially in those undergoing a spine procedural intervention, as observed in the reported case (17).…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies showed that the most common discitis-related disease was diabetes mellitus in 18 patients (16.6%), followed by ESRD in 10 (9.25%) (14). A systematic review and other reports concluded that ESRD has a positive relationship with discitis through repeated vascular access (15,16). Uremia in ESRD may alter immune status characterized by immunodepression and increased likelihood of infection, especially in those undergoing a spine procedural intervention, as observed in the reported case (17).…”
Section: Discussionmentioning
confidence: 49%
“…One potential explanation is that the aforementioned diseases lead to reduced immunocompetency; hence, the cellular immunity decreases, with reduced chemotaxis, phagocytosis, and bactericidal activity of neutrophilic granulocytes [ 23 ]. In addition, patients with chronic renal failure already have high levels of inflammatory markers in the blood due to the reduction in the number of T cells and cytokine levels; hence, a delayed or missed diagnosis might occur [ 24 ]. Therefore, when such patients visit the emergency unit, clinicians should be mindful of the fact that inflammatory processes are linked to an increased risk of spinal infection [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a delayed reduction in the number of T cells and cytokine levels is observed as compared to younger patients who receive complete adult dosing. 19 …”
Section: Review Of Literaturementioning
confidence: 99%